Histopathological Correlates of NAFLD in PCOS: Correlation with Serum Creatinine, eGFR, and Urinary Albumin Levels - Razwan Ashraf, Hamid Nawaz Khokhar, Asma Jamil, Sheema Khan, Lubna Khan, Ifrah Zafar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is increasingly recognized as a major metabolic complication in women with polycystic ovary syndrome (PCOS), yet its association with early renal dysfunction remains underexplored in South Asian populations. Objective: This study aimed to evaluate the histopathological severity of NAFLD in PCOS and determine its correlation with serum creatinine, estimated glomerular filtration rate (eGFR), and urinary albumin levels. Methods: A cross-sectional analytical study was conducted from March 2022 to February 2023 at Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and the Department of Gynaecology & Obstetrics, KRL Hospital Islamabad, enrolling 100 women with PCOS diagnosed by Rotterdam criteria. All participants underwent clinical assessment, biochemical testing, ultrasonography, and liver histopathology (in consenting cases). Renal function was evaluated through serum creatinine, eGFR (CKD-EPI), and early-morning urinary albumin measurements. Results: NAFLD was detected in 85% of participants, with Grade I being most common. Increasing NAFLD severity showed a significant rise in serum creatinine and urinary albumin, along with a notable decline in eGFR. Histopathological grading demonstrated strong positive correlations with serum creatinine (r = 0.59) and urinary albumin (r = 0.71), and a negative correlation with eGFR (r = –0.64). Conclusion: NAFLD severity in PCOS is strongly associated with early renal impairment, indicating that renal dysfunction may begin long before overt chronic kidney disease develops. Integrating hepatic and renal screening could improve early detection and risk stratification in this high-risk population. Keywords: NAFLD; Polycystic Ovary Syndrome; PCOS; Serum Creatinine; eGFR; Urinary Albumin; Hepatic Steatosis; Renal Dysfunction; Metabolic Syndrome; Histopathology